Political System Reform through the Abolition of the Presidential Threshold: An Analysis of Constitutional Court Decision Number 62/PUU-XXII/2024 - Wendy Melfa; Renaldy Eka Putra (Fakultas Hukum Universitas Lampung, 2026)
Constitutional Court Decision No. 62/PUU-XXII/2024 declared Article 222 of Law No. 7 of 2017 on General Elections unconstitutional and without binding legal force, thereby abolishing the presidential threshold for nominating presidential and vice-presidential candidates. This study examines the implications of the decision for political system reform in Indonesia. Using a normative juridical method with statutory, conceptual, and case approaches, the study finds that the decision reflects the doctrine of open legal policy, which allows legislators to reformulate electoral regulations within constitutional limits. The abolition of the presidential threshold expands political competition, broadens leadership alternatives, and strengthens the principle of popular sovereignty. Viewed through the perspectives of responsive law and Roscoe Pound’s theory of law as a tool of social engineering, the decision serves as a catalyst for political reform by promoting a more inclusive, representative, and democratic electoral system.